Chemical and microbiological changes in the fermentation of unripe papaya - Cruz, Cleopatra R.; Perez, Presentacion T. (1968)
Unripe papaya alone and in a mixture with cabbage was fermented following the procedure for sauerkraut making. The fermentation process was followed by conducting chemical and microbiological tests at determined intervals. As fermentation progressed, pH falls steadily while total acid increased correspondingly. Unripe papaya attained a pH of 3.4 and total acid of 1.20% lactic acid while cabbage papaya mixture attained a pH of 3.2 and total acid of 1.30% lactic acid. These changes were brought about by a sequence of lactic acid bacteria namely, L. mesenteroides, L. brevis and L. plantarum. The fermentation of unripe papaya and cabbage papaya mixture was found to follow the same fermentation pattern as cabbage or sauerkraut, therefore proving that unripe papaya lends itself well to fermentation. Subjective evaluation showed the product to be crisp, pleasingly acidic and highly acceptable.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Papaya; Fermentation